2022
DOI: 10.15541/jim20210550
|View full text |Cite
|
Sign up to set email alerts
|

Halogenated Ti3C2 MXene as High Capacity Electrode Material for Li-ion Batteries

Abstract: Br -)修饰对锂离子电池中 Ti3C2 负极的原子结构、电学性质、 力学性质以及电化学性能的影响。 研究表明, Ti3C2T2 单层具有良好的结构稳定性、 力学性质和导电性质。 相比 Ti3C2F2 和 Ti3C2Br2,Ti3C2Cl2 单层具有较大的弹性模量(沿二维薄膜两个方向的弹性模量分别为 321.70 和 329.43 N/m)、较 低的锂离子扩散势垒(0.275 eV)、开路电压(0.54 V)和较大的理论存储容量(化学计量比为 Ti3C2Cl2Li6 时达 674.21 mA• h/g),这表明 Ti3C2Cl2 单层作为锂电池电极具有良好的安全稳定性和充放电速率。此外,端基氯化扩大了层间 距,这提高了 Ti3C2Cl2 中锂离子的可穿透性和快速充放电速率。本研究结果表明表面氯化的 Ti3C2 纳米薄膜是一种 很有前途的锂电池负极材料,为其它的 MXenes 基电极材料设计与开发提供了重要的设计思路。

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…This approach has been successfully used in theoretical studies of MXene materials. 47–50 For pristine Nb 2 C, the calculated average bond length of 2.18 Å and lattice constants ( a = b = 3.15 Å) are comparable to previously reported data. 51 To find the most stable configuration for the systems, the structure for each type of functionalization was fully optimized and the formation energy ( E f ) was calculated using the following equation: E f = ( E Nb 2 CT 2 − mE T − E Nb 2 C )/( m + 1)where E Nb 2 CT 2 , E Nb 2 C and E T represent the energies of functionalized Nb 2 CT 2 , pristine Nb 2 C and an isolated T atom, respectively.…”
Section: Resultssupporting
confidence: 87%
“…This approach has been successfully used in theoretical studies of MXene materials. 47–50 For pristine Nb 2 C, the calculated average bond length of 2.18 Å and lattice constants ( a = b = 3.15 Å) are comparable to previously reported data. 51 To find the most stable configuration for the systems, the structure for each type of functionalization was fully optimized and the formation energy ( E f ) was calculated using the following equation: E f = ( E Nb 2 CT 2 − mE T − E Nb 2 C )/( m + 1)where E Nb 2 CT 2 , E Nb 2 C and E T represent the energies of functionalized Nb 2 CT 2 , pristine Nb 2 C and an isolated T atom, respectively.…”
Section: Resultssupporting
confidence: 87%
“…The as-obtained lowest Li-ion diffusion barriers of pure TiCrC and TiMoC monolayers onto the Ti surface were 0.031 and 0.041 eV. 88 Similarly, surface halogenated Ti 3 C 2 MXenes were investigated using first principle and density function theory with van der Waals correction, 32 which revealed that surface halogenated Ti 3 C 2 MXenes exhibit high metallic conductivity, low diffusion barrier, and storage capacity. The surface chlorination of Ti 3 C 2 led to expansion of interlayer spacing, leading to enhancement in Li-ion accessibility and fast charge−discharge rate.…”
Section: Role Of Surface and Its Modification In Mxenementioning
confidence: 99%
“…Year by year improvement in the performance and efficiency of Li-ion batteries as well as lowering of their costs have made them promising materials for electrical energy storage . Over the past decades, the gravimetric energy density of Li-ion batteries has enhanced from 90 to 250 Wh/kg, which has led to their applications in electric vehicles, portable electronic devices, and Li-ion battery grid-based energy storage. , Over the years of development of the architecture of Li-ion batteries, several electrode materials for Li-ion batteries have been fabricated such as olivines (LiFePO 4 , i.e., LFP), layered hydroxides (Li­(Ni, Mn, Co)­O 2 , i.e., NMC), and spinels (LiMn 2 O 4 , i.e., LMO) that are typically employed as cathodes, while graphite is mostly used as anode . A polymer separator separates the anode and the cathode, and a carbonate-based organic liquid is used as an electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Among the developed LIB anode materials (such as Si, Sn, Ge, Sb, etc. ), [4][5][6][7][8][9] silicon (Si) is considered as a candidate for the next-generation anode material owing to its ultrahigh specific capacity of 3580 mA h g −1 , environmental friendliness, natural abundance and a low discharge potential (≈0.4 V vs. Li/Li + ). [10][11][12] However, there are two inherent disadvantages in Si-based materials that hinder their large-scale application as anodes for LIBs.…”
Section: Introductionmentioning
confidence: 99%